The Effect of Flipped Classroom Model Integrated with Deep Learning Approach on Students' Mathematical Problem-solving Ability - Trisnawati, Desi; Wijayanto, Zainnur (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
The purpose of this study was to determine the effect of Flipped Classroom model integrated with Deep Learning approach on students' mathematical problem solving ability. This study used a quasi-experimental approach and was quantitative in nature. The study population was 32 students of grade VI of SD Negeri 4 Klaten in the 2024-2025 school year. While the research sample was 16 students of class VI A and 16 students of class VI B. Sampling was done by total sampling method. Class VI B as the control group, while class VI A as the experimental group. The research instrument was a written test of the initial version and the final version. Based on the results of the study, the average value of the experimental class in math problem solving was 80.37 while the average value of the control class was 63.37. The research results obtained from hypothesis testing show that the Flipped Classroom model integrated with the Deep Learning approach has an influence on students' ability to solve math problems because the sig. value of 0.000 <0.05. So H1 is accepted and Ho is rejected, meaning that there is an effect of the Flipped Classroom model integrated with the Deep Learning approach on students' mathematical problem solving ability.